Bioanalytical aspects of clinical mass balance studies in oncology. (December 2011) - Dubbelman, Anne-Charlotte; Rosing, Hilde; Schellens, Jan HM; Beijnen, Jos H
Clinical mass balance studies aim to investigate the absorption, distribution, metabolism and excretion (ADME) of a(n) (often radiolabeled) drug, following a single administration to humans. They are perfectly suited to determine the disposition and major metabolic pathways of a drug, the exposure to the parent drug and its metabolites, and the rate and route of elimination. A mass balance study, however, poses interesting challenges to the analysis of parent drug and metabolites in different biological matrices. Using recent clinical mass balance studies in oncology as an example, this review focuses on the aspects of mass balance studies, from bioanalytical assay development, analysis of clinical samples to reporting of study results. Along the way, it discusses bioanalytical problems and practical solutions.